Laser cladding study - Liew, Shan Wei (Nanyang Technological University, 2024)
an overview of laser cladding process. It focuses on the background of additive manufacturing, the laser cladding process that is being integrated in both CNC and robotic arm, high speed laser metal deposition. It covers the specimen materials that is being used in the process such as metal alloys, cladding materials and metal matrix composite. The report also provides the way that the material specimens are being prepare from the printing process to polishing to the hardness test that was conducted at the end. A study of 3 thermal properties and the way each thermal properties were being tested were provided in this report which is thermal shock, thermal cycle and thermal fatigue. Designing of the thermal cycle test in both manual and automated ways. The thermal cycle test results for manual method are being recorded and will be discussed. In the end, the report offers insights into the future development for this project.